The Impact of Diesel/LPG Dual Fuel on Performance and Emissions in a Single Cylinder Diesel Generator - Aydin, Mustafa; Irgin, Ahmet; Çelik, M. Bahattin (MDPI AG, 2018)
Compared to other engines of the same size, diesel engines are more economical in addition to their ability to generate high power. For this reason, they are widely used in many fields such as industry, agriculture, transportation, electricity generation. The increasing environmental concerns and diminishing oil resources led researchers to improve fuel consumption and emissions. In this context, the usage of Liquefied Petroleum Gas (LPG) fuel in diesel engines is one of the important research subjects that has been keeping up to date. This paper investigates the effects of LPG direct injection towards the end of air inlet period on engine emissions and performance characteristics. A four-stroke, air cooled, single cylinder diesel engine was modified to direct injection of LPG for diesel/LPG dual fuel operation. An Electronic Control Unit (ECU) was designed and used to adjust LPG injection timing and duration. LPG injection rates were selected as 30%, 50% and 70% on a mass base. The test engine was operated at 3000 rpm constant engine speed under varying load conditions. Throughout the experiments, it was observed that smoke density significantly reduced on the dual-fuel operation, compared to the pure diesel operation. Carbon Monoxide (CO) and Hydrocarbon (HC) emissions decreased by 30% and 20%, respectively. Brake Specific Fuel Consumption (BSFC) decreased by 8%. Nitrogen Oxide (NOx) emissions increased by 6% while effective efficiency increased up to 1.25%.
Keywords: diesel engine; LPG direct injection; diesel/LPG dual fuel; performance; emissions; 13. Climate action; 7. Clean energy